PEMBERIAN VITAMIN PADA PENYAKIT MATA - Jacobs, George E.; Sumual, Harry J. G.; Rares, Laya M. (e-CliniC, 2015)
Abstract: Vitamin intervention is known as a part of efforts to prevent the organ damages due to ocular diseases. However, ocular side effects associated with vitamin therapy has been reported, frequently. This study aimed to discover vitamin therapy and its relevancy in ocular diseases. This was a retrospective descriptive study which was conducted at the Department of Ophthalmology, General Hospital of Prof. Dr. R. D. Kandou Manado from November – December 2014. Population consisted of 435 medical records from July – September 2014. History of vitamin therapy was observed in 5 samples. Glaucoma suspect with NutriVision™ (relevant/irrelevant), KSS (Kearns-Sayre syndrome) with vitamin B1 and B +C complex (relevant), PACG (primary angle closure glaucoma) + Keratopathy with vitamin B+C comp (irrelevant), PACG + Pseudophakic post SICS (small incision cataract surgery) with Enervon-C™ (irrelevant), and NTG (normal-tension glaucoma) with NutriVision™ (relevant). Conclusion: There were relevant vitamin therapies as well as irrelevant vitamin therapies in ocular diseases. Therefore, a vitamin therapy is still be argued whether it is relevant or irrelevant in ocular diseases.Keywords: vitamin therapy, ocular diseasesAbstrak: Intervensi vitamin dikenal sebagai salah satu upaya untuk mencegah kerusakan organ mata, namun tak jarang hal ini dapat menyebabkan efek samping pada mata. Penelitian ini bertujuan untuk mengetahui dampak pemberian vitamin dan relevansinya pada penyakit mata. Penelitian dilakukan di Poliklinik Ilmu Penyakit Mata BLU RSUP Prof. Dr. R. D. Kandou pada bulan November – Desember 2014 dengan metode penelitian deskriptif retrospektif. Populasi penelitian ialah 435 data rekam medik periode Juli – September 2014. Hasil penelitian memperlihatkan 5 sampel dengan riwayat terapi vitamin. Glaucoma suspect dengan terapi multivitamin NutriVision™ (relevan/tidak relevan), KSS (Kearns-Sayre syndrome) dengan terapi vitamin B1 dan B + C kompleks (relevan), PACG (primary angle closure glaucoma) + Keratopati dengan terapi vitamin B + C kompleks (tidak relevan), PACG + Pseudofakia post SICS (small incision cataract surgery) dengan terapi multivitamin Enervon-C™ (tidak relevan) dan NTG (normal-tension glaucoma) dengan terapi multivitamin NutriVision™ (relevan). Simpulan: Terdapat pemberian vitamin baik yang relevan maupun yang tidak relevan dengan penyakit mata. Pemberian vitamin masih diperdebatkan apakah relevan atau tidak dengan penyakit mata.Kata kunci: pemberian vitamin, penyakit mata